1962
DOI: 10.1039/df9623300107
|View full text |Cite
|
Sign up to set email alerts
|

Energy distribution among reaction products. Part 1.—The reaction atomic hydrogen plus molecular chlorine

Abstract: Infra-red chemiluminescence from the reaction Hf Cl2 +HClt+ Cl (HClt is vibrationally excited HC1 in its ground electronic state) has been examined with improved resolution at roughly two orders of magnitude lower HCl pressure than heretofore. Under stationary state conditions the rotators in vibrational levels 1 to 4 appear to be in thermal equilibrium (135175°C) up to J = 7.There is, however, an excess of rotators in rotational levels J = 9, 10, 11, . . . of v = 2, 3 and 4 (v = 1 was not measured to J>9). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1964
1964
2000
2000

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The observed population, N v, is related to the specific chemical rate, k (v), into vibrational level v, by the following general stationary state equation. 50 [Normally all quantum numbers referring to product states are primed to distinguish them from reactant states. To avoid confusion the primes have been omitted in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The observed population, N v, is related to the specific chemical rate, k (v), into vibrational level v, by the following general stationary state equation. 50 [Normally all quantum numbers referring to product states are primed to distinguish them from reactant states. To avoid confusion the primes have been omitted in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The stationary-state distribution for the lowest H-atom concentration is very similar to that obtained in Charters and Polanyi's experiments (2). The factors governing relative vibrational stationarji-state concentrations in Charters and Polanyi's experiments were adjudged to be the rates of chemical reaction into each vibrational level, the rates of radiation into and out of each level, and the rate of removal from the vessel by pumping.…”
Section: Variation In H -A T O M Concentrationmentioning
confidence: 54%
“…Even normal thermal collisions, however, would have a high collision efficiency. In Section 1, it will be shown that the translational-rotational temperature of the bulk of the gas is 1250 f 50 OK. At this temperature reaction [2], which has a n activation energy of ca. 6 Itcal/mole, would occur every 10-100 collisions (assunling a steric factor of 1-0.1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations